2014
DOI: 10.22499/2.6401.004
|View full text |Cite
|
Sign up to set email alerts
|

Secondary circulations in rotating-flow boundary layers

Abstract: The rotating-flow boundary layer is a special case of the more general threedimensional boundary layer in which the pressure gradient imposed by the outer flow (above the boundary layer) is not in the same direction as the outer flow. The rotating-flow boundary layer thus has motion that is transverse to the streamlines of the outer flow, that is, there is a secondary circulation to the primary circulation of the outer flow. That the secondary circulation can extend far above the boundary layer presents a set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…In the case of tropical cyclones, such an eye is readily identified in satellite images by the absence of cloud cover. Despite their common appearance, there is still little agreement as to the mechanisms of eye formation [3][4][5], and indeed it is not even clear that the same basic mechanisms are responsible in different classes of atmospheric vortices [6]. In the absence of such a fundamental understanding, one cannot reliably predict when eyes should, or should not, form.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of tropical cyclones, such an eye is readily identified in satellite images by the absence of cloud cover. Despite their common appearance, there is still little agreement as to the mechanisms of eye formation [3][4][5], and indeed it is not even clear that the same basic mechanisms are responsible in different classes of atmospheric vortices [6]. In the absence of such a fundamental understanding, one cannot reliably predict when eyes should, or should not, form.…”
Section: Introductionmentioning
confidence: 99%
“…3c,3d,8c,and 8d in LWL20. This alternative inflow-outflow-inflow (and the associated subgradient-supergradient-subgradient wind) structure is the well-known inertial oscillation of a rotating flow with a frictional boundary layer or a process related to the gradient wind adjustment comprehended in the literature (e.g., Rotunno 2014;Stern et al 2020). Since the outflowing supergradient air becomes subgradient near the RMW and thus does not spin up the tangential wind therein.…”
Section: Main Mechanism For Axisymmetric Tc Intensificationmentioning
confidence: 97%
“…[1,2] make three additional assumptions. We will make the same assumptions here so as not to introduce additional complexity when comparing with their published solutions: (1) in evaluating V(r, z) from the azimuthally-averaged tangential wind in the WRF model, we take its value at 490 m altitude and extend that value downward so as to be independent of z below 490 m; (2) we assume a stress-free boundary condition on the disturbance horizontal velocity at z = 0; (3) we neglect the F r forcing term, and its vertical counterpart F z , keeping only F λ and Q, i.e., using only Equations (6) and (10).…”
Section: A Forced Axisymmetric Convective Ring Model Revisitedmentioning
confidence: 99%
“…The time derivatives are computed as centered differences using data at hours 28 and 26. No formal accuracy is lost here by using the residual method because it has the same accuracy as a direct evaluation of F λ and Q from Equations (5), (6) and (10). (To address a possible question about the potential inaccuracy of the residual method, for obtaining the partial time derivative terms using relatively coarse (1 h) model output, we have found that in Equations (12) and (13), the forcing terms F λ and Q are dominated by the vertical and horizontal advection terms, and are relatively insensitive to the time derivatives and therefore still less sensitive to the precise time interval used to evaluate the finite differences.…”
Section: A Forced Axisymmetric Convective Ring Model Revisitedmentioning
confidence: 99%